Cold-formed high strength steel tubular beam-columns. (1st March 2021) - Ma, Jia-Lin; Chan, Tak-Ming; Young, Ben
Highlights: A study on cold-formed high strength steel tubular beam-columns was conducted. Second order effects were considered by taking into account of the mid-height deflections. The compression and bending capacities were assessed against predictions from the American, Australian and European standards. Finite element modelling methodology on cold-formed high strength steel tubular beam-columns was presented. Abstract: High strength steel is used more often in a variety of civil engineering applications due to its high strength-to-weight ratio and cost effectiveness. This paper presents the experimental investigation on cold-formed high strength carbon steel tubular members subjected to combined compression and bending. The nominal 0.2% proof stresses of the test specimens were 700 and 900 MPa. The test specimens consisted of square hollow sections (SHS), rectangular hollow sections (RHS) and circular hollow sections (CHS). The material properties, global geometric imperfections of the specimens were measured. The behaviour of the beam-column members was investigated through testing 32 specimens which had a nominal member length of 1480 mm. The second order effects were also considered by measuring the mid-height deflections for all specimens. The compression and bending capacities, load-deformation histories and failure modes of the test specimens were also reported. The test results were compared with the values predicted from the American, Australian and European standards. Improved design recommendation is provided for cold-formed high strength steel tubular beam-columns. Based on the experimental results, finite element modelling methodology is also proposed.